Cerdas Finansial Menuju Masa Keemasan: Mengungkap Dampak Literasi, Tabungan, Dan Tekfin Terhadap Perencanaan Pensiun Di Kalangan Pekerja Industri - Wahyuni, Etty Sri; Yadewani, Dorris; Zafira, Naila (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The problems of workers in urban areas such as Batam are very complex. The readiness of workers in Indonesia to welcome the end of productive age, transition from labour to self-employment or to other jobs to fulfil household needs. Retirement planning is a lifelong process to achieve financial security in the future. Therefore, personal financial management determines readiness in good retirement planning. The problem of retirement planning comes from people's low financial literacy in financial management, plus no retirement preparation savings, besides that the use of financial technology is currently not optimally utilised by the community. The purpose of this study is to analyse and determine the effect of financial literacy, saving behaviour and financial technology on retirement preparation both directly and mediated by financial behaviour. The research method uses a quantitative associative approach to test the influence between variables with quantitative data. The number of research samples was 400 respondents who were workers in Batam City. The data analysis technique uses the Strutural Equation Model with the SEM-PLS Version 4.0 Statistical Tool. The findings of this study found that there is a significant direct influence between financial literacy, saving behaviour and financial technology variables on financial behaviour. However, a significant direct effect on retirement planning is only found in the direct effect of financial literacy and financial behaviour, while saving behaviour and financial technology do not have a significant direct effect on retirement planning. Financial behaviour functions as an intervening variable in this study, because significant research results were obtained for the indirect effect between financial literacy, saving behaviour and financial technology variables on retirement planning through financial behaviour.